تصميم وتنفيذ دارة ملائمة تتيح استخدام البيئة البرمجية الـLABVIEW"" في أنظمة التحكّم الصناعي - Nbhan, Ayman (Latakia University Journal -Engineering Sciences Series, 2018)
This research focuses on the design of a data acquisition system based on the design and implementation of a data acquisition circuit for the transmission of sensor signals (digital and analog) from the control system inputs directly to the LabVIEW, which also sends control commands directly to the digital and analog outputs,in order to take advantage of LabVIEW’s advanced features in industrial control systems.As well as to define the circuit designed within the LabVIEW librariesso that the program to communicate with the circuit designed easily and simply. This work has its importance from a technical point which simplified the design steps of the data collection system, that enables the use ofLabVIEW in industrial control, in addition to the economic terms of providing this systemthrough local manufacturing and do not need to import its commercial equipment (especially in the economic and scientific blockade of our country).To ensure that the system is functioning properly, we have implemented the data collection circuit designed, in order to study the stability of the designed circuit inputs and outputswe tested it to control the speed of the DC motor. تصميم وتنفيذ دارة ملائمة تتيح استخدام البيئة البرمجية الـLabVIEW"" في أنظمة التحكّم الصناعي يتمحور العمل في هذا البحث حول تصميم نظام تجميع للبيانات انطلاقاً من تصميم وتنفيذ دارة تحصيل للمعطيات تقوم على نقل إشارات التحسس(الرقمية والتشابهية) الموجودة على مداخل نظام التحكّم بشكل مباشر إلى البيئة البرمجية الـLabVIEW""والتي تقوم بدورها بإرسال أوامر التحكّم مباشرة إلى مُشغّلات الخرج الرقمية والتشابهية، وذلك بهدف الاستفادة من المميزات والخصائص المتقدمة التي تتمتع بها بيئة الـLabVIEW"" في أنظمة التحكّم الصناعية. وكذلك القيام بتعريف الدارة المُصممة ضمن مكتبات برنامج الـLabVIEW"" كي يتمكن البرنامج من مخاطبة الدارة المُصممة بشكل سهل وبسيط. يتميز هذا العمل بأهميته التي تتمثل بالجانب الفني من حيث وضع خطوات التصميم، بشكل مبسط، لنظام تحصيل للمعطيات يتيح استخدام البيئة البرمجية "اللابفيو" الهامة في مجال التحكّم الصناعي، إضافة إلى الجانب الاقتصادي المُتمثل في توفير هذا النظام من خلال التصنيع المحلي له وعدم الحاجة لاستيراد أجهزته التجارية (خصوصاً في ظل الحصار الاقتصادي والعلمي الذي يعاني منه بلدنا في الآونة الأخيرة).للتأكد من صحة عمل النظام تم بتنفيذ دارة تحصيل المعطيات المُصممة ومن ثم ربطها بالبيئة البرمجية الـLabVIEW""، ومن أجل دراسة استقرار مداخل ومخارج الدارة المُصممة تم باختبارها عملياً للتحكّم بسرعة محرك تيار مستمر.